The mobility of researchers as a manifestation of academic entrepreneurship based on the example of the University of Gdansk - Dobrowolska Emilia (Management, 2016)
In the knowledge economy the mission of a university, besides high quality teaching, is scientific research and the search for innovative solutions. This paper refers to an interview with the Head of the Department of Science and International Cooperation at the University of Gdansk and annual reports of the University of Gdansk’s vice-chancellor for 2006-2014. Initiating cooperation with foreign research centres, the mobility of researchers and the ability to implement international research shows that the university is striving to become an entrepreneurial university.